FROM COHESION TO COHERENCE: HOW DO THEY ATTAIN TEXT TEXTURE? - Hawa, Faiza; Sukmaningrum, Rahmawati; Senowarsito, Senowarsito; Setyaji, Arso (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2025)
Having good writing competence is essential for both students and professionals for writing reports, completing academic assignments, and expressing ideas. However, to be able to write well, writers often face various challenges related to text structure, logical flow, and interference from the native language structure especially when writing in a foreign language. The logical flow in writing can be effectively realized through cohesion and coherence in the text. The objective of this research is to know the realization of both grammatical and lexical cohesion, and coherence strategies employed by students in their writing to perform text texture. This research adopts a qualitative descriptive design using a content analysis (document review) approach. The data were obtained from documents in the form of narrative paragraphs written by English department students. The data were analyzed using the cohesion theory of Halliday and Hasan (1976). The results of the analysis show that the students applied grammatical cohesion in the form of references (55.93%), substitution (0%), conjunctions (33.05%), and ellipsis (11.01%), as well as lexical cohesion in the form of reiteration (56.04%) and collocation (43.96%) in their writing. As for coherence, the students employed strategies such as the repetition of key words (35.07%), the use of pronouns (2.65%), the use of transitions (30.89%), and logical order (8.59%). These results reflect the quality of students’ writing and demonstrate how their flow of ideas are organized coherently and cohesively, resulting in messages to be well-delivered, clear, and unambiguous.